Alveolar surfactant and adult respiratory distress syndrome: Pathogenetic role and therapeutic prospects - Seeger, W. (Clin Investig, 1993)
The adult respiratory distress syndrome (ARDS) is characterized by extended inflammatory processes in the lung microvascular, interstitial, and alveolar compartments, resulting in vasomotor disturbances, plasma leakage, cell injury, and complex gas exchange disturbances. Abnormalities in the alveolar surfactant system have long been implicated in the pathogenetic sequelae of this life-threatening syndrome. This hypothesis is supported by similarities in pulmonary failure between patients with ARDS and preterm babies with infant respiratory distress syndrome, known to be triggered primarily by lack of surfactant material. Mechanisms of surfactant alterations in ARDS include: (a) lack of surface-active compounds (phospholipids, apoproteins) due to reduced generation/release by diseased pneumocytes or to increased loss of material (this feature includes changes in the relative composition of the surfactant phospholipid and/or apoprotein profiles); (b) inhibition of surfactant function by plasma protein leakage (inhibitory potencies of different plasma proteins have been defined); (c) “incorporation” of surfactant phospholipids and apoproteins into polymerizing fibrin upon hyaline membrane formation; and (d) damage/inhibition of surfactant compounds by inflammatory mediators (proteases, oxidants, nonsurfactant lipids). Alterations in alveolar surfactant function may well contribute to a variety of pathophysiological key events encountered in ARDS. These include decrease in compliance, ventilation-perfusion mismatch including shunt flow due to altered gas flow distribution (atelectasis, partial alveolar collapse, small airway collapse), and lung edema formation. Moreover, more speculative at the present time, surfactant abnormalities may add to a reduction in alveolar host defense competence and an upregulation of inflammatory events under conditions of ARDS. Persistent atelectasis of surfactant-deficient and in particular fibrin-loaded alveoli may represent a key event to trigger fibroblast proliferation and fibrosis in late ARDS (“collapse induration”). Overall, the presently available data on surfactant abnormalities in ARDS lend credit to therapeutic trials with transbronchial surfactant administration. In addition to the classical goals of replacement therapy defined for preterm infants (rapid improvement in lung compliance and gas exchange), this approach will have to consider its impact on host defense competence and inflammatory and proliferative processes when applied in adults with respiratory failure.